FDI and economic growth: Revisiting the role of energy consumption and financial development - Noraina Mazuin, Sapuan; Mohamed, Khaled Al-Sayed; Nazirah, Hassan (GBMR, 2020)
Purpose: Foreign direct investment (FDI) is one of the driving forces highlighted in the literature that have a significant impact on economic growth, although its significance in the context of Yemen is relatively unclear. Hence, the aim of this study is to investigate the cointegration and short run relationship between FDI and its determinants especially energy consumption and financial development in Yemen. Design/methodology/approach: This study utilises a semi-annual time series data from 1990 to 2014. The Autoregressive Distributed Lag (ARDL) method was used to explore the cointegration of FDI with its determinants in Yemen.